Product and Price Analysis on Consumer Satisfaction of Halo Card Users at Telkomsel Company (Case Study of Halo Card Users in Makassar) - Rifai, Didit Fachri (Transpublika Publisher, 2025)
Indonesia's telecommunications industry faces intense competition, requiring operators to focus on customer satisfaction through strategic product and pricing decisions. The specific impact of these factors on PT. Telkomsel's Halo Card users in regional markets like Makassar remains underexplored, necessitating targeted research to understand consumer satisfaction drivers. This study aims to analyze the Product and Price variables on Consumer Satisfaction in using Halo Cards at PT. Telkomsel in Makassar, and provide input for the company while serving as reference material for future research. The analytical method used is descriptive statistical method with multiple regression analysis using SPSS software. This study applies multiple regression analysis to evaluate whether product and price factors significantly influence consumer satisfaction of HALO Card users at PT. Telkomsel Makassar. The sampling method used is Simple Random Sampling with a sample size of 100 respondents. Data is analyzed quantitatively using Multiple Linear Regression Analysis, R-Square, F-Test, and T-Test. The results of this study show that Product (X1) and Price (X2) variables partially and simultaneously have a positive influence on consumer decisions in purchasing duck-type Suzuki motorcycles at PT. Sinar Galesong Pratama in Makassar. This shows that the contribution of these two variables to consumer satisfaction is 75.0%, while the remaining 25.0% is influenced by other variables beyond the study.